Les effets « établissements » dans l’éducation au développement durable : une analyse secondaire de l’enquête PISA 2018 - Léa Chimène (Recherches en Éducation)
Since the advent of education for sustainable development, schools have been entrusted with a new mission, that of developing sustainable skills in learners. As a result of inter-national prescriptions, all education systems are invited to take up this major challenge of the 21st century, making the school a key player in the acquisition of sustainable values and skills. If schools, particularly through their organisation, composition or pedagogical choices, can have an effect on the cognitive skills of pupils, the question arises as to their impact on the development of "sustainable" skills in young people. Based on data from the PISA 2018 survey, our results show a positive but limited effect of schools on the acquisition of sustainable skills and values.